Clinical Outcomes after Reverse Total Shoulder Arthroplasty According to Primary Diagnosis - Kim, Jung Youn (Clin Orthop Surg, 2020)
BACKGROUND: To compare the clinical outcomes of reverse total shoulder arthroplasty (RTSA) according to the primary diagnosis. METHODS: In 98 shoulders (97 patients), RTSA was performed for cuff tear arthropathy (45), massive rotator cuff tear without glenohumeral arthritis (31), posttraumatic arthritis (9), primary osteoarthritis (6), rheumatoid arthritis (4), and arthritis due to infection sequelae (3). The average age of the patients at surgery was 68.9 years (range, 46–84 years). The mean follow-up duration was 48.4 months (range, 24–85 months). RESULTS: In the overall series, the mean subjective pain score (visual analog scale) during motion decreased from 5.2 preoperatively to 1.8 at 2 years of follow-up. There were significant improvements in active forward flexion (preoperatively 51.5° to 121.8° at 2 years of follow-up). The average Constant score improved from 35.4 points to 57.8 points and UCLA score improved from 13.4 points to 28.8 points. The Constant score and UCLA score were 60.8 and 31.0 points, respectively, in patients with rheumatoid arthritis. The Constant score and UCLA score were 58.4 and 29.1 points, respectively, in patients with cuff tear disease and 55.7 and 27.7 points, respectively, in patients with posttraumatic arthritis. Patients' subjective satisfaction was 86.8 points in the overall series; highest in the patients with arthritis by infection sequelae (96.7 points) and lowest in the patients with posttraumatic arthritis (82.2 points). In terms of complications, there were 17 cases (17.3%) of scapular notching and 2 patients with suprascapular nerve irritation symptom, but no patients with permanent neuropathy. CONCLUSIONS: The range of forward flexion and abduction motion, pain relief, and functionality were improved after RTSA in not only patients with cuff tear disease but also those with other arthritic diseases. There was no difference in the clinical outcomes of RTSA between patients with cuff tear disease and those with other arthritic diseases.